A A: A - Ataboyev, Isroil (Журнал иностранных языков и лингвистики, 2022)
The acquisition of a foreign language by adult learners is often slow, discouraging and even frustrating. All learners want to use the foreign language with confidence and spontaneity, in the same way they use their mother tongue. The teacher who works with adult learners has to perform a thorough analysis of his/her students in order to get to know them better.